Distributed Strategies for Computational Sprints. - Songchun Fan; Zahedi, Seyed Majid; Lee, Benjamin C. (Communications of the ACM, 2019)
Computational sprinting is a class of mechanisms that boost performance but dissipate additional power. We describe a sprinting architecture in which many, independent chip multiprocessors share a power supply and sprints are constrained by the chips’ thermal limits and the rack’s power limits. Moreover, we present the computational sprinting game, a multi-agent perspective on managing sprints. Strategic agents decide whether to sprint based on application phases and system conditions. The game produces an equilibrium that improves task throughput for data analytics workloads by 4–6× over prior greedy heuristics and performs within 90% of an upper bound on throughput from a globally optimized policy.